Defect engineering oxygen vacancies via synergistic tungsten substitution and water quenching in V2O5 cathodes for high-performance zinc-ion batteries - Jianwei Wang; Lin Xu; Yating Yu; Jianzhao Liu; Qianhui Zhang; Wenlin Zhang; Xinyue Wang; Jihong Bian; Yanzhong Zhen; Daniel Q. Tan (Chemical Engineering Journal, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Balancing efficacy and safety: Inorganic and organic Fe-Ca Co-interventions reduce oral Cd bioavailability from rice and their impacts on gut health - Xin-Ying Lin; Hong-Bo Li; Duo-Duo Jiao; Lu Zhou; Bo Xu; Albert Juhasz; Lena Q. Ma; Dongmei Zhou (Journal of Hazardous Materials, 2026)

Sulfonated azobenzene-derived nanogels: Hypoxia-specific degradation enables superior nucleic acid-mediated tumor therapy - Jia Zhou; Shubo Du; Lan Wang; Qiong Wu; Changmin Yu; Wei Du; Lin Li; Shao Q. Yao (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Water availability modulates maximum canopy heights of low-elevation Amazonian second-growth forests - Midhun Mohan; Gilberto Z. Pastorello; Yanlei Feng; Esmaeel Adrah; Michael Keller; Ewane Basil Ewane; Marcos Longo; Ovidiu Csillik; Antonio Ferraz; Abhilash Dutta Roy; Lin Meng; Jeffrey Q. Chambers (Tropical Ecology, 2026)
Tropical second-growth forests of the Amazon sequester large amounts of carbon and are important carbon sinks, contributing substantially to climate change mitigation, biodiversity conservation, and providing crucial ecosystem services. Deforestation due to selective logging and shifting cultivation is expanding second-growth forest areas in tropical forest regions, which if well managed, regenerate rapidly over time. Maximum forest canopy height is an important metric of biomass and carbon accumulation in second-growth forests and is strongly influenced by water availability. The water limitation hypothesis explains the positive influence of water availability on maximum tree heights and has been examined and demonstrated at a small-scale using field data, and at a global scale, with limited accuracy, using remote sensing data in tropical ecosystems. However, this hypothesis concerning maximum canopy height has not been much studied at regional and national scales for tropical second-growth forests. In this study, we leveraged NASA GEDI spaceborne lidar data across the Brazilian Amazon and derived second-growth forest relative height metrics for delineating the influence of water availability, second-growth forest age, and topographic elevation on maximum canopy height. Water availability was found to significantly influence the maximum canopy height of second-growth forest trees, of age range from 30 to 35 years, at elevations less than 500 m and maximum precipitation thresholds of 1500 mm. Our results indicate that changing precipitation patterns or increased drought conditions under different climate change regimes could impact forest structure, plant communities, ecosystem functioning, and carbon sequestration capabilities of tropical second-growth forests in the Amazon.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Consumption of fermented Cd and Pb contaminated wheat flour increases potential health risk - Weiqin Xing; Zhexu Si; James A. Ippolito; Guobing Lin; Farzana Kastury; Sen Ma; Kunyan Qiu; Linlin Zhao; Lena Q. Ma; Liping Li (Food and Chemical Toxicology, 2025)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Revealing how urban morphology at urban planning and design stage influence energy using urban building energy model - F. Lin; L. Luo; Q. Gu; S. Hao; W. Wang (International Journal of Environmental Science and Technology, 2025)

Driving factors of summer diurnal surface thermal environment in subtropical coastal cities: a Shenzhen case study - Q. Guo; Y. Lin; S. Zhong; X. Zhang (International Journal of Environmental Science and Technology, 2025)

Comparison of indoor hydroponic plants for decarbonization and cooling performance: the field experiment of three vegetation species - G. Zhang; Q. Lin; X. Li; H. Xia; H. Li (International Journal of Environmental Science and Technology, 2025)

Retraction notice to ‘Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals’ [Sci. Total Environ., 926 (2024) 171859] - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Health risk assessment of dietary cadmium exposure based on cadmium bioavailability in food: Opportunities and challenges - Di Zhao; Guo-Bin Lin; Chenjing Liu; Albert L. Juhasz; Lena Q. Ma (Journal of Hazardous Materials, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Experimental study on macro spray, combustion and emission characteristics of biodiesel and diethyl carbonate blends - L. Zhao; X. Zhu; R. Zhao; J. Tian; D. Qian; Q. Lin (International Journal of Environmental Science and Technology, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Source specific fine particles and rates of asthma and COPD healthcare encounters pre- and post-implementation of the Tier 3 vehicle emissions control regulations - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; Philip K. Hopke; David Q. Rich (Journal of Hazardous Materials, 2025)

Efficient activation of UV-driven ozonation using ultrasonics for LDPE decomposition - A. Pattanateeradetch; C. Sakulthaew; Y.-T. Lin; A. Watcharenwong; A. Žgajnar Gotvajn; Y.-C. Chen; Q. Xu; C. Chokejaroenrat (Journal of Water Process Engineering, 2025)

High geological background concentrations of As and Cd in karstic soils may not contribute to greater risks to human health via rice consumption - Guobing Lin; Chao Zhang; Zhongfang Yang; Yong Li; Chenjing Liu; Lena Q. Ma (Journal of Hazardous Materials, 2024)

DGT and kinetic analyses differentiate Se and Cd bioavailability in naturally enriched paddy soils - Chao Zhang; Dong-Xing Guan; Paul N. Williams; Guo-Bing Lin; Xiao-Lei Chen; Lena Q. Ma (Chemosphere, 2024)

PM2.5 and its components and respiratory disease healthcare encounters – Unanticipated increased exposure-response relationships in recent years after environmental policies - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Philip K. Hopke; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; David Q. Rich (Environmental Pollution, 2024)

Reducing the overpotential of overall water spitting by micro-pump-like electrode engineering - Tianbiao Zeng; Jie Lin; Biao Wang; Binbin Guo; Yihong Ding; Chang Q Sun (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Microplastic co-exposure elevates cadmium accumulation in mouse tissue after rice consumption: Mechanisms and health implications - Shan Chen; Haijun Gan; Xinying Lin; Boxuan Wang; Mengya Li; Lena Q. Ma; Dongmei Zhou; Hongbo Li (Journal of Hazardous Materials, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Hysteresis area at the canopy level during and after a drought event in the Central Amazon - Bruno O. Gimenez; Daisy C. Souza; Niro Higuchi; Robinson I. Negrón-Juárez; Israel de Jesus Sampaio-Filho; Alessandro C. Araújo; Adriano J.N. Lima; Clarissa G. Fontes; Kolby J. Jardine; Charles D. Koven; Lin Meng; Gilberto Pastorello; et al. (Agricultural and Forest Meteorology, 2024)

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Biocontrol of strawberry Botrytis gray mold and prolong the fruit shelf-life by fumigant Trichoderma spp. - Q. S. Fan; H. J. Lin; Y. J. Hu; J. Jin; H. H. Yan; R. Q. Zhang (Biotechnology Letters, 2024)

RETRACTED: Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Sex-dependent effects of rice cadmium exposure on body weight, gut microflora, and kidney metabolomics based on a mouse model - Jin-Lei Yang; Shan Chen; Jin-Feng Xi; Xin-Ying Lin; Rong-Yue Xue; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2024)

Biogeochemical behavior of selenium in soil-air-water environment and its effects on human health - Z. N. Xu; Z. Q. Lin; G. S. Zhao; Y. B. Guo (International Journal of Environmental Science and Technology, 2024)

Generating high spatial resolution exposure estimates from sparse regulatory monitoring data - Yihui Ge; Zhenchun Yang; Yan Lin; Philip K. Hopke; Albert A. Presto; Meng Wang; David Q. Rich; Junfeng Zhang (Atmospheric Environment, 2023)

The effect of polychlorinated biphenyls extracted from offshore sediments on the intestinal epithelium and microflora of zebrafish - M. Zhang; D-H Zhu; Q-L Song; M-M Chen; Y Hu; D-J Kang; Z-B Chen; H-Y Lin; F-H Nie; J-J Chen (International Journal of Environmental Science and Technology, 2023)

Corrigendum to “Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni” [J Hazard Mater 452 (2023) 131367] - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Succession of biochar addition for soil amendment and contaminants remediation during co-composting: A state of art review - Huu-Tuan Tran; Nanthi S. Bolan; Chitsan Lin; Quach An Binh; Minh-Ky Nguyen; The Anh Luu; Van-Giang Le; Cham Q. Pham; Hong-Giang Hoang; Dai-Viet N. Vo (Journal of Environmental Management, 2023)

A monitoring system for CO2-EOR and storage based on reactive transport simulation of CO2 migration in groundwater - L. Li; Y. Wu; Q. Lin; Q. Wen; S. Chong (International Journal of Environmental Science and Technology, 2023)

Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Characteristics and correlation of soil low-molecular-weight organic acids and nutrients in four plantations in red soil area of south China - Y. M. Ren; Z. J. Hou; T. Su; Z. R. Lin; A. Q. Liu; L. P. Cai (International Journal of Environmental Science and Technology, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Ammonium removal characteristics of Delftia tsuruhatensis SDU2 with potential application in ammonium‑rich wastewater treatment - L. F. Chen; L. X. Chen; D. Pan; Y. L. Ren; J. Zhang; B. Zhou; J. Q. Lin; J. Q. Lin (International Journal of Environmental Science and Technology, 2023)

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

Bacterial coculture enhanced Cd sorption and As bioreduction in co-contaminated systems - Huaiting Liu; Zhiqi Hong; Jiahui Lin; Dan Huang; Lena Q. Ma; Jianming Xu; Zhongmin Dai (Journal of Hazardous Materials, 2023)

Triggering of ST-elevation myocardial infarction by ultrafine particles in New York: Changes following Tier 3 vehicle introduction - Catherine S. Yount; Mark J. Utell; Philip K. Hopke; Sally W. Thurston; Shao Lin; Frederick S. Ling; Yunle Chen; David Chalupa; Xinlei Deng; David Q. Rich (Environmental Research, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Effect of pyrolysis temperature on pyrolysis of pine saw dust and application of bio-char - J. Lin; Q. Zhang; H. Xia; S. Cheng (International Journal of Environmental Science and Technology, 2022)

Petrological and isotopic data from Eocene granites in the Luocang area, South Lhasa terrane, Tibet: implications for the India–Eurasia collision - J.-G. Gao; F. Ding; J.-Q. Lin; Q.-H. Zhu; Y. Sun; X.-G. Xie (Australian Journal of Earth Sciences, 2021)

Evaluation of favourable hot dry rock areas in the east of the Yishu fault zone in China - Q. Deng; A. Jiang; Z. Tong; H. Lin; Z. Gao; X. Sun; M. Nie (Australian Journal of Earth Sciences, 2021)

Genotyping-by-sequencing to determine the genetic structure of a Tibetan medicinal plant Swertia mussotii Franch. - Yan Qiao; Fengxian Guo; Naxin Huo; Lin Zhan; Jiaqing Sun; Xixi Zuo; Zeguang Guo; Yong Q. Gu; Yi Wang; Yue Liu (Genetic Resources and Crop Evolution, 2021)

Adaptive transgenerational effects remain significant - Yuan‐Ye Zhang; Junjie Yin; Ming Zhou; Zeru Lin; Qingshun Q. Li (Ecology Letters, 2020)
The comment by Sánchez‐Tójar et al . (2020, Ecol Lett) questioned the methodology, transparency and conclusion of our study (Ecol Lett, 22, 2019, 1976). The comment has overlooked important evolutionary assumptions in their reanalysis, and the issues raised were in fact dealt with through the peer‐review process. Far from being biased, the key conclusion of our meta‐analysis still stands; transgenerational effects are largely adaptive.

Active ingredients of Inula helenium L. exhibits similar anti-cancer effects as isoalantolactone in pancreatic cancer cells - Y. Y. Yan; Q. Zhang; B. Zhang; B. Yang; N. M. Lin (Natural Product Research, 2020)

Sedimentary environment and facies of the Huagang Formation in the northern central Xihu Depression, East China Sea Basin, China - Z. X. Zhao; C. M. Dong; C. Y. Lin; X. G. Zhang; X. Huang; B. J. Li; W. Guo; Z. Q. Zhu (Australian Journal of Earth Sciences, 2020)

Transgenerational effects benefit offspring across diverse environments: a meta‐analysis in plants and animals - Junjie Yin; Ming Zhou; Zeru Lin; Qingshun Q. Li; Yuan‐Ye Zhang (Ecology Letters, 2019)
The adaptive value of transgenerational effects (the ancestor environmental effects on offspring) in changing environments has received much attention in recent years, but the related empirical evidence remains equivocal. Here, we conducted a meta‐analysis summarising 139 experimental studies in plants and animals with 1170 effect sizes to investigate the generality of transgenerational effects across taxa, traits, and environmental contexts. It was found that transgenerational effects generally enhanced offspring performance in response to both stressful and benign conditions. The strongest effects are in annual plants and invertebrates, whereas vertebrates appear to benefit mostly under benign conditions, and perennial plants show hardly any transgenerational responses at all. These differences among taxonomic/life‐history groups possibly reflect that vertebrates can avoid stressful conditions through their mobility, and longer‐lived plants have alternative strategies. In addition to environmental contexts and taxonomic/life‐history groups, transgenerational effects also varied among traits and developmental stages of ancestors and offspring, but the effects were similarly strong across three generations of offspring. By way of a more comprehensive data set and a different effect size, our results differ from those of a recent meta‐analysis, suggesting that transgenerational effects are widespread, strong and persistent and can substantially impact the responses of plants and animals to changing environments.

What Promotes the Recovery of Salt Marsh Infauna After Oil Spills? - J. W. Fleeger; M. R. Riggio; I. A. Mendelssohn; Q. Lin; D. R. Deis; D. S. Johnson; K. R. Carman; S. A. Graham; S. Zengel; A. Hou (Estuaries and Coasts, 2019)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

Pharmacodynamic and Pharmacokinetic Properties of AFPep, a Novel Peptide for the Treatment of Breast Cancer - J. A. Bennett; W. Mansouri; Q. Lin; P. Feustel; T. T. Andersen (International Journal of Peptide Research and Therapeutics, 2018)

Formation and characteristics of the Xiaoba landslide in Fuquan, Guizhou, China - F. Lin; L. Z. Wu; R. Q. Huang; H. Zhang (Landslides, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Simulated differences in 21st century aridity due to different scenarios of greenhouse gases and aerosols - L. Lin; A. Gettelman; Q. Fu; Y. Xu (Climatic Change, 2018)

Microbial dolomite in the sabkha environment of the middle Cambrian in the Tarim Basin, NW China - X. L. You; S. Sun; C. S. Lin; J. Q. Zhu (Australian Journal of Earth Sciences, 2018)

Formation of chlorite rims and the impact of pore-lining chlorite on reservoir quality: a case study from Shiqianfeng sandstones in upper Permian of Dongpu Depression, Bohai Bay Basin, eastern China - P. J. Ma; C. Y. Lin; S. Q. Zhang; C. M. Dong; Y. F. Xu (Australian Journal of Earth Sciences, 2017)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

A bacterial infection by Vibrio harveyi causing heavy reduction of cultured lined seahorse Hippocampus erectus - G Qin; X Wang; S Tan; Q Lin (Journal of Fish Diseases, 2017)

Genetic Diversity of Populations of Saccharum spontaneum with Different Ploidy Levels Using SSR Molecular Markers - X. L. Liu; X. J. Li; C. H. Xu; X. Q. Lin; Z. H. Deng (Sugar Tech, 2016)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Differentiation in development of benzimidazole resistance in Colletotrichum gloeosporioides complex populations from strawberry and grape hosts - T. Lin; X. F. Xu; D. J. Dai; H. J. Shi; H. D. Wang; C. Q. Zhang (Australasian Plant Pathology, 2016)

A novel pathogenic bacteria ( Vibrio fortis ) causing enteritis in cultured seahorses, Hippocampus erectus Perry, 1810 - X Wang; Y Zhang; G Qin; W Luo; Q Lin (Journal of Fish Diseases, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Soil Nitrous oxide and Carbon dioxide emissions following incorporation of above- and below-ground biomass of green bean - M. Shaaban; Q. Peng; R. Hu; S. Lin; J. Zhao (International Journal of Environmental Science and Technology, 2016)

Development and evaluation of a loop‐mediated isothermal amplification assay for the detection of channel catfish virus - G X Liu; L Lin; M Wang; X Q Liu (Journal of Fish Diseases, 2015)

Influence of Regional Difference in Bone Mineral Density on Hip Fracture Site in Elderly Females by Finite Element Analysis - Z. L. Lin; P. F. Li; Z. H. Pang; X. H. Zheng; F. Huang; H. H. Xu; Q. L. Li (Cell Biochemistry and Biophysics, 2015)

Rapid generation and analysis of expressed sequence tags to uncovering inflorescence secondary metabolism of Bougainvillea spectabilis ‘Speciosas’ by pyrosequencing - S. X. Xu; Q. Y. Huang; C. S. Lin; F. C. Lin; L. X. Lin; Q. Y. Shen (Euphytica, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

A Review of the Genus Pielomastax Chang (Orthoptera: Eumastacoidea) from China with Description of a New Species - L L Lin; Z M Zheng; R Yang; S Q Xu (Neotropical Entomology, 2014)

Production GH transgenic goat improving mammogenesis by somatic cell nuclear transfer - Q. Zhang; J. Q. Chen; J. Lin; Q. H. Yu; H. Q. Yu; X. J. Xu; G. H. Liu; Q. Yang (Molecular Biology Reports, 2014)

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

Is the isentropic surface always impermeable to the potential vorticity substance? - Chanh Q. Kieu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2012)

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

The effect of the expression of virulence-associated DEAD-box RNA helicase mRNA on the imbalance of Th1-Th2 cytokines in the CSF of patients with Cryptococcus neoformans meningitis - L. Jiang; N. Lin; Z. Cheng; B. Yang; Q. Ou (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Kinetic migration of isothiazolinone biocides from paper packaging to Tenax and Porapak - Q.-B. Lin; T.-J. Wang; H. Song; R.-Z. Wang (Food Additives & Contaminants: Part A, 2011)

Determination of silver in nano-plastic food packaging by microwave digestion coupled with inductively coupled plasma atomic emission spectrometry or inductively coupled plasma mass spectrometry - Q.-B. Lin; B. Li; H. Song; H.-J. Wu (Food Additives & Contaminants: Part A, 2011)

Effect of DEM mesh size on AnnAGNPS simulation and slope correction - Xiaoyan Wang; Q. Lin (Environmental Monitoring and Assessment, 2011)

Migration of silver from nanosilver–polyethylene composite packaging into food simulants - H. Song; B. Li; Q.-B. Lin; H.-J. Wu; Y. Chen (Food Additives & Contaminants: Part A, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

Long-term changes of dissolved oxygen, hypoxia, and the responses of the ecosystems in the East China Sea from 1975 to 1995 - X. Ning; C. Lin; J. Su; C. Liu; Q. Hao; F. Le (Journal of Oceanography, 2011)

Interval-fuzzy stochastic optimization for regional energy systems planning and greenhouse-gas emission management under uncertainty—a case study for the Province of Ontario, Canada - Q. G. Lin; G. H. Huang (Climatic Change, 2011)

Analysis of isothiazolinone biocides in paper for food packaging by ultra-high-performance liquid chromatography–tandem mass spectrometry - Q.-B. Lin; T.-J. Wang; H. Song; B. Li (Food Additives & Contaminants: Part A, 2010)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

Functional evaluation of therapeutic response for a mouse model of medulloblastoma - Aislynn K. Samano; Sachiko Ohshima-Hosoyama; Thomas G. Whitney; Suresh I. Prajapati; Aoife Kilcoyne; Eri Taniguchi; William W. Morgan; Laura D. Nelon; Ai-Ling Lin; Osamu Togao; Inkyung Jung; Brian P. Rubin; et al. (Transgenic Research, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Seroprevalence of Toxoplasma gondii infection in breeding sows in Western Fujian Province, China - C. Q. Huang; Y. Y. Lin; A. L. Dai; X. H. Li; X. Y. Yang; Z. G. Yuan; X. Q. Zhu (Tropical Animal Health and Production, 2010)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

The occurrence of the feline “Candidatus Mycoplasma haemominutum” in dog in China confirmed by sequence-based analysis of ribosomal DNA - Q. J. Zhuang; H. J. Zhang; R. Q. Lin; M. F. Sun; X. J. Liang; X. W. Qin; W. J. Pu; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population - F. Lin; S. L. Xue; D. G. Tian; C. J. Li; Y. Cao; Z. Z. Zhang; C. Q. Zhang; Z. Q. Ma (Euphytica, 2008)

Expression and significance of PTEN and VEGF in canine mammary gland tumours - C. W. Qiu; D. G. Lin; J. Q. Wang; C. Y. Li; G. Z. Deng (Veterinary Research Communications, 2008)

Note: Anti-viral activity ofAilanthus altissima crude extract onRice stripe virus in rice suspension cells - J. G. Yang; Y. G. Dang; G. Y. Li; L. J. Guo; W. T. Wang; Q. W. Tan; Q. Y. Lin; Z. J. Wu; L. H. Xie (Phytoparasitica, 2008)

Uptake of Different Species of Iodine by Water Spinach and Its Effect to Growth - Huan-Xin Weng; Ai-Lan Yan; Chun-Lai Hong; Lin-Li Xie; Ya-Chao Qin; Charles Q. Cheng (Biological Trace Element Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Soil hydraulic manipulation and organic amendment for the enhancement of selenium volatilization in a soil–pickleweed system - B. Shrestha; S. Lipe; K. A. Johnson; T. Q. Zhang; W. Retzlaff; Z.-Q. Lin (Plant and Soil, 2006)

Detection of Hong Kong 97-like H5N1 influenza viruses from eggs of Vietnamese waterfowl - Y. Li; Z. Lin; J. Shi; Q. Qi; G. Deng; Z. Li; X. Wang; G. Tian; H. Chen (Archives of Virology, 2006)

Genetic and physical mapping of Pi36(t), a novel rice blast resistance gene located on rice chromosome 8 - X. Q. Liu; L. Wang; S. Chen; F. Lin; Q. H. Pan (Molecular Genetics and Genomics, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Identification of a 98-kb DNA segment containing the rice Eui gene controlling uppermost internode elongation, and construction of a TAC transgene sublibrary - Y.-H. Xu; Y.-Y. Zhu; H.-C. Zhou; Q. Li; Z.-X. Sun; Y.-G. Liu; H.-X. Lin; Z.-H. He (Molecular Genetics and Genomics, 2004)

Optimum Nitrogen Use and Reduced Nitrogen Loss for Production of Rice and Wheat in the Yangtse Delta Region - D.J. Wang; Q. Liu; J.H. Lin; R.J. Sun (Environmental Geochemistry and Health, 2004)

A new potyvirus from tuberose ( Polianthes tuberosa ) in China - L. Lin; H.-Y. Zheng; J. Chen; J.-P. Chen; Q.-Y. Zhang; M.-F. Zhao; J. F. Antoniw; M. J. Adams (Archives of Virology, 2004)

Behavior of Cu and Zn under combined pollution of 2,4-dichlorophenol in the planted soil - Y.X. Chen; Q. Lin; Y.F. He; G.M. Tian (Plant and Soil, 2004)

EDTA and industrial waste water improving the bioavailability of different Cu forms in contaminated soil - Y.X. Chen; J.Y. Shi; W.D. Zhang; Q. Lin; G.M. Tian (Plant and Soil, 2004)

Predicted ATP-binding cassette systems in the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; H. Wang; R. W. Hammond; R. Jomantiene; Q. Liu; S. Lin; B. A. Roe; R. E. Davis (Molecular Genetics and Genomics, 2004)

Microbial biomass carbon, nitrogen and phosphorus in the soil profiles of different vegetation covers established for soil rehabilitation in a red soil region of southeastern China - F.E. Wang; Y.X. Chen; G.M. Tian; S. Kumar; Y.F. He; Q.L. Fu; Q. Lin (Nutrient Cycling in Agroecosystems, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

Thallium Concentration in Lake Trout from Lake Michigan - T.-S. Lin; J. Nriagu; X.-Q. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

X-ray absorption spectroscopy study shows that the rapid selenium volatilizer, pickleweed (Salicornia bigelovii Torr.), reduces selenate to organic forms without the aid of microbes - A. Lee; Z.-Q. Lin; I. Pickering; N. Terry (Planta, 2001)

Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

RFLP mapping of QTLs conferring salt tolerance during germination in an interspecific cross of tomato - M. R. Foolad; F. Q. Chen; G. Y. Lin (Theoretical and Applied Genetics, 1998)

Changes in nitric oxide synthase isoforms in the spinal cord of rat following induction of chronic arthritis - J. Wu; Q. Lin; Y. Lu; W. D. Willis; K. N. Westlund (Experimental Brain Research, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Stimulation of thymidine kinase activity in baculovirus infected cells is not due to a virus-coded enzyme - X. Wang; W. Xie; Q. Long; D. He; G. Lin; Y. Pang; Z. Pu (Archives of Virology, 1992)